Implementation of Embedded PID Controller to Water Level Control System - Kajaman, Aboajela; Saleh, Zeiad; Sahal, Khalifa (International Journal of Advanced Multidisciplinary Research and Studies, 2024)
In chemical and industrial processes, the level control of liquids in tanks is significant and widely used, especially in power stations and petroleum industries. The liquid level can be controlled by the most common method, PID control due to its efficiency and performance in achieving the desired set point. In this paper, the water level in tank control using a level sensor and PID controller system will be designed and implemented based on the PID Arduino microcontroller algorithm that controls the change in flow rate by controlling a DC water pump with the help of a MOSFETs interface circuit. Tuning the specific PID level tank controller will be implemented to increase the system accuracy with no error and overshoot when there is a disturbance (drawn or excess water).